If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20y + 2 = 46 Reorder the terms: 2 + 20y = 46 Solving 2 + 20y = 46 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 20y = 46 + -2 Combine like terms: 2 + -2 = 0 0 + 20y = 46 + -2 20y = 46 + -2 Combine like terms: 46 + -2 = 44 20y = 44 Divide each side by '20'. y = 2.2 Simplifying y = 2.2
| 1.33*4=y | | s*7-17=137 | | x^2+x+m-1=0 | | 5(x+3)-3=2(x+8) | | 43-4=y | | 9h-16=74 | | 9m-15=58 | | 5n^2+7n=-2 | | 8x+12y-20= | | 40+16x= | | 3(25-10h+h^2)-20+4h-(75-20)= | | 15x-28= | | 0=x^2-16x-225 | | 6x+27= | | x^7=65 | | 4.9x^2-20x=0 | | 8+(y+2)=4(y-3) | | x+(x*0.25)=500000 | | 3n+4-4=n+20 | | 4t^2-9s^2=0 | | lnx^2-6lnx+5=0 | | (5x-2)-(3x-1)=(4x+3)-(5x-2) | | 7(-1+h)-5(-1)= | | 2lnx+ln(2x-3)=ln(3x-2) | | 0.63=logx | | 3(-5+h)-4(-5)= | | 3(25-2h+h^2)-4+4h-(4-3)= | | 9b^2+42bg+49g^2= | | 3(25-2h+h^2)-4+4h-(3-4)= | | 7(1-2h+h^2)-5+5h-(7-5)= | | 20n=60 | | y=192+1.04y |